2008
DOI: 10.7773/cm.v34i2.1246
|View full text |Cite
|
Sign up to set email alerts
|

Induced spawning and larval rearing of spotted rose snapper, Lutjanus guttatus, at the Marine Biology Station, Puntarenas, Costa Rica

Abstract: Wild spotted rose snapper, Lutjanus guttatus (n = 400, 60–100 g), were captured and grown out in cages during one year (February 2001 to February 2002). When the mature stage was detected by cannula samples, females (n = 9) were induced to spawn with a total dose of 1600 IU of human chorionic gonadotropin (HCG) per kilogram of body weight, given in two injections (56% and 44% of the total dose). Males received only one injection of 200 IU HCG kg–1 body weight, at the time of the second female injection. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
3
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 11 publications
3
19
3
19
Order By: Relevance
“…Survival rates of the spotted rose snapper larvae during the rearing period were improved in this study, compared to those of previous trials conducted in 600‐L cylindrical fiberglass tanks (Garcia‐Ortega et al 2005; Abdo‐de la Parra et al 2010), and the average survival rate achieved for this species in Costa Rica (Boza‐Abarca et al 2008; Herrera‐Ulloa et al 2010). High mortality occurred during two critical periods: at the start of the exogenous feeding phase, as reported for spotted rose snapper by Boza‐Abarca et al (2008) and for other snapper species (Lim et al 1985; Emata et al 1994; Duray et al 1996; Tucker 1998); and during metamorphosis, which in itself is a stressor in fish larvae (Kraul et al 1993). These two critical periods are common in other marine fish species (Tucker 1998).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Survival rates of the spotted rose snapper larvae during the rearing period were improved in this study, compared to those of previous trials conducted in 600‐L cylindrical fiberglass tanks (Garcia‐Ortega et al 2005; Abdo‐de la Parra et al 2010), and the average survival rate achieved for this species in Costa Rica (Boza‐Abarca et al 2008; Herrera‐Ulloa et al 2010). High mortality occurred during two critical periods: at the start of the exogenous feeding phase, as reported for spotted rose snapper by Boza‐Abarca et al (2008) and for other snapper species (Lim et al 1985; Emata et al 1994; Duray et al 1996; Tucker 1998); and during metamorphosis, which in itself is a stressor in fish larvae (Kraul et al 1993). These two critical periods are common in other marine fish species (Tucker 1998).…”
Section: Discussioncontrasting
confidence: 43%
“…This species reaches high prices and the demand significantly exceeds fishery supply. Aquaculture research on spotted rose snapper has been mostly focused on induced spawning (Valverde Chavarría and Boza Abarca 1999; Ibarra‐Castro and Duncan 2007; Boza‐Abarca et al 2008; Ibarra‐Castro and Alvarez‐Lajonchère 2009), although there has been progress in improving juvenile mass production (Alvarez‐Lajonchère et al 2010). Herrera‐Ulloa et al (2010) reported the production of 70,000 spotted rose juveniles in 1 yr (this being the first juvenile mass production of this species), considered an important breakthrough after a joint effort of several institutions for 5 yr, which allowed the establishment of a grow‐out pilot farm in the Gulf of Nicoya, Costa Rica.…”
mentioning
confidence: 99%
“…Se evaluó el uso del extracto de pituitaria de carpa en la maduración y desove de hembras silvestres de pargo manchado Lutjanus guttatus (Valverde, 1999;Valverde y Boza, 1998) y el efecto de la hormona gonadotropina coriónica humana (GCH) y del extracto de pituitaria de L. guttatus en la maduración in vitro de ovocitos de esta especie (López, 2004). Las técnicas aplicadas permitieron lograr desoves naturales y desoves inducidos utilizando la hormona GCH en hembras maduras de L. guttatus (Boza-Abarca, Calvo-Vargas, Solís-Ortiz & Komen, 2008). Posteriormente, se evaluó la inducción hormonal en peces silvestres y criados en jaulas flotantes de L. guttatus utilizando una suspensión de pituitaria de carpa y GCH.…”
Section: Líneas De Investigación Desarrolladas § Moluscosunclassified
“…Ibarra-Castro & Duncan (2007) detailed the commercial importance of snapper species, and other authors have explained the interest of aquaculture and fishing industries in developing snapper culture (Tucker & Jory, 1991;Leu et al, 2003;Dumas et al, 2004;Ogle & Lotz, 2006;Boza-Abarca et al, 2008;Castillo-Vargasmachuca et al, 2007;Boza-Abarca et al, 2011;CastilloVargasmachuca et al, 2012;Alvarez-Lajonchere et al, 2012). Growing this species in cage protected sites or open sea (Bergheim, 2012) and ponds on land has been considered as a future possibility.…”
mentioning
confidence: 99%
“…In Latin America, snapper species have been assessed and recommended for mariculture activities because they are easy to manipulate, accept artificial feed, and are not aggressive when they are maintained in high densities (Arnold et al, 1978;Tucker & Jory 1991;Boza-Abarca et al, 2008). Ibarra-Castro & Duncan (2007) detailed the commercial importance of snapper species, and other authors have explained the interest of aquaculture and fishing industries in developing snapper culture (Tucker & Jory, 1991;Leu et al, 2003;Dumas et al, 2004;Ogle & Lotz, 2006;Boza-Abarca et al, 2008;Castillo-Vargasmachuca et al, 2007;Boza-Abarca et al, 2011;CastilloVargasmachuca et al, 2012;Alvarez-Lajonchere et al, 2012).…”
mentioning
confidence: 99%